Growth and yield response of Watani Wado job's tears (Coix lacryma-jobi L.) to the application frequency of phosphate fertilizer and paclobutrazol in different growing seasons - Mahdya, Arifa Syahanna; Farahdillah, Rizka; Kadapi, Muhamad; Nurmala, Tati (Universitas Padjadjaran, 2024)
Job's tears (Coix lacryma-jobi L.) is a carbohydrate source functional food crop that can be developed as a substitute for rice. This study aims to determine the best application frequency of phosphate (P) fertilizer and paclobutrazol for supporting the growth and yield of job's tears in both rainy and dry seasons. The research was conducted from November 2021 - November 2022 at the Ciparanje research station and Laboratory Centre Universitas Padjadjaran, Jatinangor, Sumedang. The experiment used a randomized block design (RBD) consisting of P fertilizer application frequency (once, twice, and thrice) and paclobutrazol application frequency (once, twice, and thrice) and three replications.. The best season was determined using the T-test. The results showed that there was no interaction between growth components and job's tears yield in both rainy and dry season planting. P fertilizer application had a significant effect on lateral branch per tiller in the rainy season and root-shoot ratio in the dry season. Paclobutrazol application had a significant effect on the number of tillers per plant and number of seeds per plant in the rainy season, and the lateral branch per tiller in the dry season. Planting in the rainy season had the best growth and yield components compared to the dry season.